Tyrosol attenuates pro-inflammatory cytokines from cultured astrocytes and NF-κB activation in in vitro oxygen glucose deprivation. (December 2018) - Luo, Gang; Huang, Yinuo; Mo, Dapeng; Ma, Ning; Gao, Feng; Song, Ligang; Sun, Xuan; Xu, Xiaotong; Liu, Lian; Huo, Xiaochuan; Wang, Bo; Li, Xiaoqing; et al.
Abstract: Subsequent inflammation in stroke plays an important role in the damage of neurons in the perilesional area. Therapeutic intervention targeting inflammation may be a promising complementary strategy to current treatments of stroke. Here, we explored the possible beneficial effects of tyrosol, a derivative of phenethyl alcohol and natural antioxidant, playing an anti-inflammatory role in astrocyte culture and in vitro oxygen glucose deprivation (OGD) model. MTT, western blot, ELISA and EMSA assays were carried out to investigate cell viability, protein expression level, cytokine expression and NF-κB activity. We found tyrosol protected cultured astrocytes against OGD-induced cell viability loss in MTT test. Meanwhile, tyrosol attenuated the released TNF-α and IL-6 level from astrocyte via regulating Janus N-terminal kinase (JNK). The reduction of cytokines from astrocyte might be due to its inhibition of astrocyte activation and regulation of STAT3 signaling pathway since tyrosol attenuated the expression level of GFAP (glial fibrillary acidic protein) and the phosphorylation of STAT3. Additionally, we demonstrated that tyrosol prevented the degradation of IκBα and the increase of IκBα phosphorylation in astrocytes exposed to OGD, which led to the suppression of NF-κB function during ischemia. Collectively, our results showed that tyrosol may be a promising complementary treatment compound for stroke via modulating the inflammatory response in astrocytes during ischemia. Highlights: OGD induces the release of cytokines from astrocytes. Tyrosol attenuates the neuroinflammation of astrocytes. Tyrosol suppresses NF-κB function of astrocytes under OGD. Tyrosol may be a promising supplementary treatment compound for stroke.